TAC3 and TACR3 defects cause hypothalamic congenital hypogonadotropic hypogonadism in humans - Young, Jacques; Bouligand, Jerome; Francou, Bruno; Raffin-Sanson, Marie-Laure; Gaillez, Stephanie; Jeanpierre, Marc; Grynberg, Michael; Kamenicky, Peter; Chanson, Philippe; Brailly-Tabard, Sylvie; Guiochon-Mantel, Anne (The journal of clinical endocrinology and metabolism, 2010)
Context: Missense loss-of-function mutations in TAC3 and TACR3, the genes encoding neurokinin B and its receptor NK3R, respectively, were recently discovered in kindreds with nonsyndromic normosmic congenital hypogonadotropic hypogonadism (CHH), thus identifying a fundamental role of this pathway in the human gonadotrope axis. Objective: The objective of the study was to investigate the consequences on gonadotrope axis of TAC3 deletion and TACR3 truncation in adult patients with normosmic complete CHH. Results: We identified three unrelated patients with the same homozygous substitution in the TAC3 intron 3 acceptor splicing site (c.209-1G>C) and three siblings who bore a homozygous mutation in the TACR3 intron 2 acceptor splicing site (c.738-1G>A). We demonstrated that these two mutations, respectively, deleted neurokinin B and truncated its receptor NK3R. We found in three patients with TAC3 mutation originating from Congo and Haiti a founding event in a more distant ancestor by means of haplotype analysis. We calculated that time to this common ancestor was approximately 21 generations. In several patients we observed a dissociation between the very low LH and normal or nearly normal FSH levels, this gonadotropin responding excessively to the GnRH challenge test. This particular hormonal profile, suggests the possibility of a specific neuroendocrine impairment in patients with alteration of neurokinin B signaling. Finally, in these patients, pulsatile GnRH administration normalized circulating sex steroids, LH release, and restored fertility in one subject. Conclusion: Our data demonstrate the hypothalamic origin of the gonadotropin deficiency in these genetic forms of normosmic CHH. Neurokinin B and NK3R therefore both play a crucial role in hypothalamic GnRH release in humans.